The State as a force according to Alessandro Passerin D’Entreves - Basali, Rogério A. de Mello (Argumentos - Revista de Filosofia, 2011)
This paper presents results of a doctorate research about the political thought of Alessandro Passerin D ́Entreves and brings introductory considerations to the State doctrine formulated by this author. The phenomena analyzed in the text make possible the comprehension of the State as a force, which is the first part of the State doctrine formulated by D ́Entreves.